Kinds of Support Offered by the Disability Unit to Students with Disabilities at Institutions of Higher Learning in South Africa: A Case Study of the University of Venda (Journal of Student Affairs in Africa, 2021)
More and more tertiary institutions are now focusing on the mainstreaming and inclusion of students with disabilities. Some higher education institutions (HEIs) in South Africa have established so-called Disability Units (DUs) to offer specialised services to students with disabilities, to facilitate access and integration of these students at their institutions. For many students with disabilities, the DU services are the first point of contact. These units work to facilitate access and ensure participation in the university for students with disabilities. This involves making 'reasonable adjustments' and providing support for students with disabilities to ensure full participation and equal opportunities. Students with disabilities who will need support and alternative arrangements range from students with hearing impairments, visual impairments, physical impairments, health impairments (such as chronic illness), learning impairments, or psychiatric disabilities. Although universities, both locally and internationally, may systematise support in slightly different ways, many universities follow similar trends to accommodate and support students with specific disabilities as per their needs. Appropriate support systems in teaching and learning are vital in ensuring equal access for students with disabilities. The commitment of the institution to facilitating support and participation depends on its willingness to change admission, curricular and assessment procedures, as well as physical accessibility of the institution. We have seen from the literature that support for students with disabilities varies from country to country (Lane, 2017; Mantsha, 2016). We followed a qualitative research approach and adopted a case study research design to understand the phenomenon of student support better. We used classroom observations, document analysis and focus group interviews to collect data. Ten students with disabilities participated in the study. The study found that the DU of the university played an important role in supporting their studies. However, the students did not receive adequate additionalsupport from their lecturers such as tutorials and differentiation of the curriculum. Shortage of learning materials specifically adapted for students with disabilities was mentioned as a weakness. The study recommends that lecturers should be trained on how to teach and support students with disabilities as this will enhance the quality of teaching and learning for these students. Other recommendations include that the DU should establish an online interactive portal for its registered students to increase communication between students and the university.
Keywords: disability; educational support; higher education institutions; inclusive education